A Methodology to Evaluate the Sensory Properties of Instant Hot Chocolate Beverage With Different Fat Contents: Multi-Criteria Decision-Making Techniques Approach - Dogan, Mahmut; Aslan, Duygu; Aktar, Tugba; Sarac, Meryem Goksel; Goksel Sarac, Meryem (Springer, 2016)
The multi-criteria decision-making techniques are applied in many areas such as integrated manufacturing systems, evaluation of technology investment, water and agriculture management and energy planning. However, there are very few studies in the field of food. In this work, the selection of optimum fat content in the model beverage of instant hot chocolate beverage was evaluated based on sensory analyses by performing multi-criteria decision techniques (analytic hierarchy process, simple additive weighting, technique for order preference by similarity to ideal solution and elimination et choixtraduisant la realite-elimination and choice translating reality). The wettability, solubility, bulk density, soluble solids, pH, color values, and rheological and sensory properties of the nine samples were evaluated. According to the results of multi-criteria decision techniques, sample S2 which had a relatively high amount of fat content was the most preferred beverage among the samples. Study showed that the use of different fat contents of milk and cocoa powder positively affected the rheological parameters and preferences of consumers. The findings may be considered to improve dairy and cocoa-based products formulation by the food industry.
Goksel Sarac, Meryem/0000-0002-8190-2406; Aktar, Tugba/0000-0001-8417-868X; Dogan, Mahmut/0000-0003-1639-4641
Keywords: Multi-Criteria Decision Techniques; AHP; SAW; Electre; TOPSIS; Hot Chocolate; Cocoa; Fat; Sensory; Rheology